Indonesia's Commercial Diplomacy: Footwear Export Industry - Rachmawati, Iva; Issundari, Sri; Sari, Dyah Lupita (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The increase in Indonesia's footwear export industry since 2019 has become an important marker for the success of Indonesia's commercial diplomacy in the footwear industry. Some trade and investment collaborations organized by the state are believed to be the key to the success of commercial diplomacy. Commercial diplomacy, in this context, refers to the economic activities undertaken by the state to bolster its national economy through trade and investment partnerships. Notably, non-state actors have played a crucial role in enhancing Indonesia's footwear exports by lobbying, advocating, promoting, and ensuring compliance with international standards. These actors have also contributed significantly to the industry's production innovation and human resource development. This research aims to show that non-state actors have an essential role in commercial diplomacy through a commercial diplomacy model using the experience of commercial diplomacy practices in the Indonesian footwear export industry. This research employs qualitative methods, including documentary studies and interviews, to illustrate how these non-state actors support a commercial diplomacy model. The findings indicate that their involvement facilitates trade and strengthens Indonesia's position in the global footwear market, notably as it ranks fourth among the world’s producers. By leveraging these collaborative efforts, Indonesia aims to capitalize on its historical successes and address challenges such as rising labor costs and fluctuating international demand.